Enantioselective Synthesis of Allylboronates and Allylic Alcohols by Copper-Catalyzed 1,6-Boration - Luo, Yunfei; Roy, Iain D.; Madec, Amaël G. E.; Lam, Hon Wai (Angewandte Chemie International Edition, 2014)
Chiral secondary allylboronates are obtained in high enantioselectivities and 1,6:1,4 ratios by the copper‐catalyzed 1,6‐boration of electron‐deficient dienes with bis(pinacolato)diboron (B2(pin)2). The reactions proceed efficiently using catalyst loadings as low as 0.0049 mol %. The allylboronates may be oxidized to the allylic alcohols, and can be used in stereoselective aldehyde allylborations. This process was applied to a concise synthesis of atorvastatin, in which the key 1,6‐boration was performed using only a 0.02 mol % catalyst loading. 1,6‐Borations of electron‐deficient dienes with bis(pinacolato)diboron using copper catalyst loadings as low as 0.0049 mol % provided chiral allylboronates that, after oxidation, result in allylic alcohols in high enantioselectivities and 1,6:1,4 ratios. The allylboronates can also be used in stereoselective allylations of aldehydes. This process was applied to a concise synthesis of atorvastatin.